The opening workspace control strategy of a novel manipulator-driven emission source microscopy system. (March 2023) - Liu, Xiaorui; Li, Xian; Su, Hang; Zhao, Yuefang; Ge, Shuzhi Sam
Abstract: Emission source microscopy (ESM) technique can be utilized for localization of electromagnetic interference sources in the electronic systems, but its accuracy is limited by the typical planar scanning mode. In order to increase the accuracy, this paper presents a novel cylinder-aperture ESM measurement system driven by 6-DOF manipulator, and investigated the control strategy to generate the maximum-area aperture and optimized scanning trajectory. Based on the multiple constraints of the cylinder-aperture ESM measurement, we proposes analyzing the impact of the constraints by steps. This can obtain the analytical solution of the manipulator workspace and support solving the maximum aperture area. Besides, a modified RRT*(Rapidly-exploring Random Trees) algorithm is addressed to optimize the manipulator trajectory. The simulation and tests have proven that this algorithm could obviously reduce the joint mutation and cumulative tracking error. In the experimental section, the near-field scanning (NFS) tests, planar-aperture ESM measurement and proposed cylinder-aperture ESM measurement were conducted to measure one benchmark emission source. The results have demonstrated that the cylinder-aperture ESM measurement has the best convergences on the radiation pattern of the emission source. Graphical abstract: Highlights: Propose a novel method to obtain the manipulator workspace and solve the maximum-area aperture. Employ the modified RRT* method to optimizes the ESM scanning path and decrease the tracking error. Organize the comparison experiments to prove the performance of proposed ESM method.